PLANT PHYSIOLOGY - SALISBURY, FRANK B.; ROSS, CLEON W. (New Delhi CBS Publishers, 2005)
The organization of this text is basically the same as in previous editions. We realize that beginning plant physiology students have studied the plant cell in previous courses but we have greatly expanded the discussion of the cell in our prologue. Knowledge of the cell is so fundamental that a complete review seems justified-and was requested by any re viewers. The rest of our text is divided into four sections: The first seven chapters (Section 1) deal with physical processes the middle seven chapters (Section 2) with metabolism and biochemistry and the eight chapters of Section 3 with growth and development. The last two chapters (Section 4) are built upon the other twenty-two to relate plant function to the environment that so strongly influences it. We assume that students have some knowledge of organic chemistry as background for our biochemistry section. We also assume that students have studied DNA replication and protein synthesis (molecular biology) topics usually covered in basic biology courses several topics about molecular biology for quick: review. Of course students will also have covered many other topics that we. describe; we hope our presentation will be appropriate review and reinforcement.
https://www.cbspd.co.in/plant-physiology-3ed-pb-2005
Keywords: Botany; Plant; Plant - physiology